Knee kinematics of anterior cruciate ligament rupture analyzed with single-angle video: a case report with the slip-catch motion - Nakazato, K. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: There are only a few scientific reports which describe the kinematics of anterior cruciate ligament (ACL) ruptures. The aim of this study was to describe the knee kinematics of ACL ruptures with a single-angle video.